Insight into the Polar Reactivity of the Onium Chalcogen Analogues of S-Adenosyl-l-methionine - Iwig, David F; Booker, Squire J (Biochemistry (Easton), 2004)
S-Adenosyl-l-methionine (AdoMet) is one of Nature's most diverse metabolites, used not only in a large number of biological reactions but amenable to several different modes of reactivity. The types of transformations in which it is involved include decarboxylation, electrophilic addition to any of the three carbons bonded to the central sulfur atom, proton removal at carbons adjacent to the sulfonium, and reductive cleavage to generate 5‘-deoxyadenosyl 5‘-radical intermediates. At physiological pH and temperature, AdoMet is subject to three spontaneous degradation pathways, the first of which is racemization of the chiral sulfonium group, which takes place in a pH-independent manner. The two remaining pathways are pH-dependent and include (1) intramolecular attack of the α-carboxylate group onto the γ-carbon, affording l-homoserine lactone (HSL) and 5‘-methylthioadenosine (MTA), and (2) deprotonation at C-5‘, initiating a cascade that results in formation of adenine and S-ribosylmethionine. Herein, we describe pH-dependent stability studies of AdoMet and its selenium and tellurium analogues, Se-adenosyl-l-selenomethionine and Te-adenosyl-l-telluromethionine (SeAdoMet and TeAdoMet, respectively), at 37 °C and constant ionic strength, which we use as a probe of their relative intrinsic reactivities. We find that with AdoMet intramolecular nucleophilic attack to afford HSL and MTA exhibits a pH−rate profile having two titratable groups with apparent pK a values of 1.2 ± 0.4 and 8.2 ± 0.05 and displaying first-order rate constants of <0.7 × 10-6 s-1 at pH values less than 0.5, ∼3 × 10-6 s-1 at pH values between 2 and 7, and ∼15 × 10-6 s-1 at pH values greater than 9. Degradation via deprotonation at C-5‘ follows a pH−rate profile having one titratable group with an apparent pK a value of ∼11.5. The selenium analogue decays significantly faster via intramolecular nucleophilic attack, also exhibiting a pH−rate profile with two titratable groups with pK a values of ∼0.86 and 8.0 ± 0.1 with first-order rate constants of <7 × 10-6 s-1 at pH values less than 0.9, ∼32 × 10-6 s-1 at pH values between 2 and 7, and ∼170 × 10-6 s-1 at pH values greater than 9. Degradation via deprotonation at C-5‘ proceeds with one titratable group displaying an apparent pK a value of ∼14.1. Unexpectedly, TeAdoMet did not decay at an observable rate via either of these two pathways. Last, enzymatically synthesized AdoMet was found to racemize at rates that were consistent with earlier studies (Hoffman, J. L. (1986) Biochemistry 25, 4444−4449); however, SeAdoMet and TeAdoMet did not racemize at detectable rates. In the accompanying paper, we use the information obtained in these model studies to probe the mechanism of cyclopropane fatty acid synthase via use of the onium chalcogens of AdoMet as methyl donors.